Genetic population structure of Peninsular bighorn sheep (Ovis canadensis nelsoni) indicates substantial gene flow across US–Mexico border. (April 2015) - Buchalski, Michael R.; Navarro, Asako Y.; Boyce, Walter M.; Winston Vickers, T.; Tobler, Mathias W.; Nordstrom, Lisa A.; García, Jorge Alaníz; Gille, Daphne A.; Penedo, Maria Cecilia T.; Ryder, Oliver A.; Ernest, Holly B.
Highlights: We examined the population genetics of Peninsular bighorn sheep. Three distinct genetic populations were identified in the US-Mexico border region. Substantial genetic diversity was observed at both nuclear and mitochondrial loci. Assignment tests indicate inter-population dispersal among both sexes. Low genetic differentiation suggests gene flow across the international border. Abstract: Within the United States (US), Peninsular bighorn sheep ( Ovis canadensis nelsoni, PBS) are listed as federally endangered. Despite known metapopulation structure, little is known regarding functional connectivity across the international border with Mexico. Increasing threats to connectivity associated with highway expansion, renewable energy development, and completion of the US–Mexico border fence, led us to conduct a study of genetic variation and spatial structure. Blood and fecal samples were collected ( n = 224) on both sides of the border from 1992 to 2013. Genetic data was obtained for 25 microsatellite loci and 515 base pairs of the mitochondrial DNA control region. Microsatellite diversity (observed heterozygosity = 0.56; allelic richness = 4.1; inbreeding coefficient = 0.01) was substantial despite past demographic declines. STRUCTURE analysis indicated the presence of three genetic populations, one of which spanned the international border. This pattern of genetic structure was supported by analysis of molecular variance for both microsatellites and mitochondrial DNA ( P < 0.01), and low-moderate pairwise fixation indices ( F ST = 0.09–0.15; Φ ST = 0.18–0.27) indicated substantial gene flow among populations. Migrant detection tests indicated natal dispersal occurred within both sexes, with no evidence of sex bias. Despite the severe reductions in population abundance which led to federal listing in the US, these data suggest PBS have retained substantial genetic variation and show little evidence of a recent genetic bottleneck. Patterns of genetic spatial structure indicate gene flow throughout the ranges is common, and construction of a US–Mexico border fence or wind energy infrastructure would disrupt connectivity of the metapopulation. Future conservation efforts should focus on identifying dispersal corridors and maintaining functional connectivity to facilitate recolonization of unoccupied habitat.